Algebra

posted by .

Solve the exponential equation.
4^2x – 2 = 26

I know I use the one to one property to equate. But I am confused. Thanks!

  • Algebra -

    do you mean

    4^(2x) - 2 = 26 or

    4^(2x-2) = 26 or

    (4^2)x - 2 = 26

    The way you typed it, it would be the last one, but I am sure that is not what you meant.

  • Algebra -

    4^(2x-2)=26

  • Algebra -

    then take log of both sides
    log [4^(2x-2) }= log 26
    (2x-2)log4 = log 26
    2x-2 = log26/lo4
    2x = (log26/log4 + 2)
    x = (log26/log4 + 2)/2 = appr. 2.1751

    check
    4^(2(2.1751 - 2)
    = 4^(4.35022 - 2)
    = 4^2.35022
    = 26
    = RS

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math/algebra

    solve each of the following systems by substitution. 16) 5x -2y = -5 y - 5x = 3 20) 8x -4y = 16 y = 2x - 4 28) 4x -12y = 5 -x + 3y = -1 Step one: Solve on of the equations for one of the variables. y=2x-4 Step two:Substitute the expression …
  2. Algebra

    To solve the system of equations, which expression could be substituted for x into the first equation?
  3. exponential equation-Algebra

    Solve the exponential equation. Express the solution set in terms of natural logarithms. 4^(x + 4) = 5^(2x + 5)-This question I don't understand.
  4. pre-cal: one-to-one property

    i am not sure how to do these problems... *use the one-to-one property to solve the equation for x* 1. 2^(x-2)= 1/32 2. e^(x^2-3)=e^2x
  5. Pre Cal long problem( Can I see the work on this)

    A stuffed animal dealer tells you that a fish he bought for $8 four years ago is now worth $200 follow the steps below to find the effective yield for this investment. Begin with the equation 8(1+r) ^4=200.Solve for (1+r) ^4 Take the …
  6. algebra

    2. The level of thorium in a sample decreases by a factor of one-half every 2 million years. A meteorite is discovered to have only 8.6% of its original thorium remaining. How old is the meteorite in millions of years?
  7. Geometry

    Given: 7x + 2 = 2 + 5x – 6 Prove: x = –3 Given the equation 7x + 2 = 2 + 5x – 6, use the commutative property to rearrange the terms so that like terms are next to one another. This gives the equation 7x + 2 = 2 – 6 + 5x. Then, …
  8. algebra

    1. the function f(x)=6x/3x-5 is one to one. find its inverse and check your answer. And on the second one can you tell me if I am correct. 2. solve the following exponential solution 7^2x+7^x+1-60=0 7^2 x+7^x-59=0 (49x)+7^x-59=0 49x/49=0/49 …
  9. Algebra 1--Please, help me!

    Solve the following equation by graphing the related function. 1. 4x^2 + 8x = 32 A: ?
  10. algebra

    Solving exponential and logarithmic equation. An example of an exponential equation is: Solve for x: 5^x=125

More Similar Questions